Strategi Manajemen Logistik Obat-Obatan di Instalasi Farmasi Rumah Sakit - Makmur, Afifah Idelma; Ayomi, Anasthasia F M; Rahmayati, Anisa; Purwadhi, Purwadhi; Widjaja, Yani Restiani (Universitas Pahlawan Tuanku Tambusai, 2025)
Logistics management is one operational components owned by the hospital and has a very important role. The function of logistics management includes ensuring the availability of goods that have good quality, the right amount, providing goods such as medicines on time. Some hospitals have obstacles, challenges, and problems in implementing drug logistics management. For example, delays in distribution, errors in inventory management, and inaccuracies in drug procurement planning. The purpose of writing is to provide analysis results related to the Drug Logistics Management Strategy in the Hospital Pharmacy Installation. The writing method used in writing this journal is to use the qualitative type. The results and conclusions are that the drug logistics management strategy can be carried out by considering every aspect, such as planning, procuring, storing, distributing, and the existence destruction/removal activities. In the aspect of planning, it is carried out by the management hospital pharmacy installation. Then in determining the type of drug can be done based on the formulary, requests, decisions head agency, e-catalog, diseases, the most needed drugs, and drug stocks that will run out. Logistics management in the ordering/procurement aspect is carried out when the availability of drugs is almost running out. Then in the aspect of drug storage, a special storage warehouse is implemented. In the storage model is based on the alphabetical system, FEFO, and FIFO. Then in logistics management on the removal/destruction is carried out on disposable medical materials, medical devices, and other pharmaceutical preparations that have expired and do not meet quality requirements.